Microbial community dynamics in rotational cropping: seasonality vs. crop-specific effects - Casagrande Pierantoni, Debora; Conti, Angela; Corte, Laura; Tosti, Giacomo; Benincasa, Paolo; Cardinali, Gianluigi; Guiducci, Marcello (Frontiers in Microbiology, 2025)
IntroductionSoil microbial communities are central to soil health and plant productivity, yet their responses to crop rotation and seasonal changes remain incompletely understood. Understanding how crop identity and phenology shape these communities is essential for optimizing agricultural sustainability.MethodsThis study examined how different crop species and their growth stages influence the diversity, composition, and functional characteristics of soil microbiota in a long-term crop rotation system. We integrated high-throughput DNA sequencing with soil chemical and spectroscopic analyses to assess microbial community dynamics across three key seasonal time points.ResultsOur results indicate that while crop species and their growth stages can influence microbial community structure, these effects were generally modest and variable. In contrast, seasonal factors and soil physicochemical properties—particularly electrical conductivity—exerted stronger and more consistent effects on microbial beta diversity. Despite shifts in taxonomic composition, a core microbiome dominated by Acidobacteriota and Bacillus persisted across crops and seasons. Functional predictions revealed a seasonal peak in nitrification potential during warmer months, suggesting environmental rather than crop-driven control of this process.DiscussionThese findings highlight the resilience of soil microbiomes under rotational systems and underscore the dominant role of seasonal and abiotic factors in shaping microbial community dynamics. A better understanding of these interactions can inform agricultural practices aimed at sustaining microbial functionality and promoting long-term soil health.